Experimental Investigation of Heat Transfer Enhancement in a Double Pipe Heat Exchanger Using Compound Technique of Transverse Vibration and Inclination Angle (Journal of Engineering, 2023)
Numerous tests are recently conducted to assess vibration's role in accelerating the heat transfer rate in various heat exchangers. In this work, the enhancement of heat transfer by the effect of transfer vibration and inclination angles on the surface of a double pipe heat exchanger experimentally has been investigated. A data acquisition system is applied to record the data of temperatures, flow rates, and frequencies over the tests. A compound technique was adopted, including the application of a set of inclination angles of (0°, 10°, 20°, and 30°) under the effect of frequency of vibration ranging from sub-resonance to over-resonance frequencies. The results showed that the overall heat transfer coefficient enhances by applying the compound technique at all the working fluid's temperatures and flow rate ranges. The maximum increase in overall heat transfer coefficient occurs at an angle of 30° and the resonance frequency. Moreover, the effectiveness of the double pipe heat exchanger gradually expanded when temperature, inclination angles, and vibration amplitude rosed. But the effectiveness value declined as the hot working flow rate increased considerably. Finally, the enhancement factor demonstrated that the combined strategy (vibration frequencies and inclination angles) had been the most effective technique in improving and enhancing heat transfer and was superior to the other ways. Additionally, the extremes improvement in overall heat transfer coefficient, effectiveness, and enhancement factor are 183.4, 191, and 164.4 %. The improvement was situated at the resonance frequency with a 30° inclination angle.